2017
DOI: 10.1017/s0033291716003263
|View full text |Cite
|
Sign up to set email alerts
|

The association between childhood adversities and subsequent first onset of psychotic experiences: a cross-national analysis of 23 998 respondents from 17 countries

Abstract: Background Although there is robust evidence linking childhood adversities (CAs) and an increased risk for psychotic experiences (PEs), little is known about whether these associations vary across the life-course and whether mental disorders that emerge prior to PEs explain these associations. Methods We assessed CAs, PEs and DSM-IV mental disorders in 23,998 adults in the WHO World Mental Health Surveys. Discrete-time survival analysis was used to investigate the associations between CAs and PEs, and the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 68 publications
10
117
2
2
Order By: Relevance
“…We constructed multivariable models that included a comprehensive list of 29 traumatic event types, and incorporated number of traumatic events per person, as well as interactive models. Similar to our earlier analysis of childhood adversities and psychotic experience onsets, 2 we found that not all traumatic events had equivalent associations with subsequent first onset of psychotic experiences. For example, in the marginal effect model (model 4), we found that only 12 of the 29 traumatic event types were associated with an increased risk of subsequent psychotic experiences.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We constructed multivariable models that included a comprehensive list of 29 traumatic event types, and incorporated number of traumatic events per person, as well as interactive models. Similar to our earlier analysis of childhood adversities and psychotic experience onsets, 2 we found that not all traumatic events had equivalent associations with subsequent first onset of psychotic experiences. For example, in the marginal effect model (model 4), we found that only 12 of the 29 traumatic event types were associated with an increased risk of subsequent psychotic experiences.…”
Section: Discussionsupporting
confidence: 88%
“…In keeping with previous studies of psychotic experiences, 2,6,12 we made the a priori decision to exclude individuals reporting psychotic experiences who screened positive for possible schizophrenia/psychosis and manic depression/mania (i.e. respondents who were either told by a doctor that their psychotic experiences were caused by these conditions or who were treated with antipsychotic medications for these symptoms).…”
Section: Methodsmentioning
confidence: 99%
“…Full details are given in several WMH publications including two recent papers on PEs. 9,22 Clinical reappraisal studies indicate that lifetime diagnoses based on the CIDI have good concordance with diagnoses based on blinded clinical interviews. 23 In keeping with our previous research, standardised diagnostic hierarchy rules among the disorders assessed were applied where appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Early life traumatic stressful events (TSEs) are associated with increased rates of psychopathology, above and beyond posttraumatic stress disorder (PTSD; Heim & Nemeroff, 2001;Lowe et al, 2017;McGrath et al, 2017;McLaughlin et al, 2012;Teicher, Tomoda, & Andersen, 2006). TSEs are also associated with obsessive-compulsive disorder (OCD; Boudreaux, Kilpatrick, Resnick, Best, & Saunders, 1998;Briggs & Price, 2009;De Silva & Marks, 1999;Gothelf, Aharonovsky, Horesh, Carty, & Apter, 2004;Lochner et al, 2002;Ojserkis, McKay, & Lebeaut, 2018), with rates as high as 50-70% of patients experiencing OCD symptoms following a TSE (Sadock, Sadock, & Ruiz, 2015), and with increased severity of OCD symptoms in people with a history of trauma exposure (Cromer, Schmidt, & Murphy, 2007).…”
Section: Introductionmentioning
confidence: 99%